Corticospinal tract integrity is related to primary motor cortex thinning in relapsing–remitting multiple sclerosis. (December 2015) - Bergsland, Niels; Laganà, Maria Marcella; Tavazzi, Eleonora; Caffini, Matteo; Tortorella, Paola; Baglio, Francesca; Baselli, Giuseppe; Rovaris, Marco
Background: The relationship between white matter injury and cortical atrophy development in relapsing–remitting multiple sclerosis (RRMS) remains unclear. Objectives: To investigate the associations between corticospinal tract integrity and cortical morphology measures of the primary motor cortex in RRMS patients and healthy controls. Methods: 51 RRMS patients and 30 healthy controls underwent MRI examination for cortical reconstruction and assessment of corticospinal tract integrity. Partial correlation and multiple linear regression analyses were used to investigate the associations of focal and normal appearing white matter (NAWM) injury of the corticospinal tract with thickness and surface area measures of the primary motor cortex. Relationships between MRI measures and clinical disability as assessed by the Expanded Disability Status Scale and disease duration were also investigated. Results: In patients only, decreased cortical thickness was related to increased corticospinal tract NAWM mean, axial and radial diffusivities in addition to corticospinal tract lesion volume. The final multiple linear regression model for PMC thickness retained only NAWM axial diffusivity as a significant predictor (adjusted R 2 = 0.270, p = 0.001). Clinical measures were associated with NAWM corticospinal tract integrity measures. Conclusions: Primary motor cortex thinning in RRMS is related to alterations in connected white matter and is best explained by decreased NAWM integrity.